2015
DOI: 10.1117/1.oe.54.1.013105
|View full text |Cite
|
Sign up to set email alerts
|

Artificial target detection with a hyperspectral LiDAR over 26-h measurement

Abstract: Abstract. Laser scanning systems that simultaneously measure multiple wavelength reflectances integrate the strengths of active spectral imaging and accurate range measuring. The Finnish Geodetic Institute hyperspectral lidar system is one of these. The system was tested in an outdoor experiment for detecting man-made targets from natural ones based on their spectral response. The targets were three camouflage nets with different structures and coloring. Their spectral responses were compared against those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 52 publications
(50 reference statements)
0
40
0
Order By: Relevance
“…The approach is a laboratory setup for scanning single leafs. Puttonen et al (2015) present a study on an outdoor scanning experiment with different high vegetation species. They calculate several vegetation indices relating them to leaf area index, chlorophyll in leafs and biomass estimates.…”
Section: Introductionmentioning
confidence: 99%
“…The approach is a laboratory setup for scanning single leafs. Puttonen et al (2015) present a study on an outdoor scanning experiment with different high vegetation species. They calculate several vegetation indices relating them to leaf area index, chlorophyll in leafs and biomass estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Experiences on this field have been obtained, for example, from studies with a hyperspectral laser scanner developed at the FGI (Chen et al, 2010;Hakala et al, 2012). The system is a terrestrial one and has been successfully applied for vegetation analyses and separation of man-made targets from natural ones (e.g., Puttonen et al, 2015). Phennigbauer and Ullrich (2011) discussed the development and potential of multi-wavelength ALS systems.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the use of dualwavelength data can substantially improve classification accuracy compared to one-wavelength data. More extensive discussions and reference lists on these earlier developments of multispectral laser scanning can be found, for example, in Puttonen et al (2015) and Wichmann et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…This HSL system possesses the high 3-dimensional and abundant spectral properties capability, which has been applied in many practical fields. Especially in the vegetation biochemical parameter estimation, it has showed considerable advantages and potential (Hakala et al, 2012;Li et al, 2014;Puttonen et al, 2015;Nevalainen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%